Pengembangan Game Edukasi Fractal Adventure untuk Pembelajaran Bilangan Pecahan - Leo Wahyudi; Iskandar Wiryokusumo; Achmad Noor Fatirul (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2021)
Research conducted produced educational game media that uses a computer system. In this day and age, many children are busy playing games to get rid of boredom. Then it is necessary to develop learning media that utilize whatever is popular with children such as educational games with the aim of attracting attention and increasing the effectiveness of learning. The purpose of this development can provide educational game media that has been declared valid by material experts, instructional media experts, and field practitioners to support fraction learning. This study uses the Gerlach and Ely learning model. The results of the validation statement of material experts were 86%, the results of the validations of learning media experts were 82% and field practitioners were 93%, for students' responses to fractal adventure education games for learning fraction numbers including very decent criteria.